Molecular epidemiology and comparative genomics of carbapenemase-producing Escherichia coli isolates from 19 tertiary hospitals in China from 2019 to 2020 - Ko, Weihsin; Tseng, Songlu; Chou, Chiahsin; Li, Tianmeng; Li, Rose; Zhang, Yaqiao; Li, Yun; Lv, Yuan (Frontiers in Microbiology, 2023)
Background The clinical use of carbapenems is facing challenges due to increased carbapenemase-producing Escherichia coli (CP-EC) infections over the past decade. Meanwhile, whole-genome sequencing (WGS) is an important method for bacterial epidemiological research. We aim to provide more gene-based surveys to explore the genomics and occurrence of CP-EC in China. Methods A total of 780 Escherichia coli isolates were collected by the China Antimicrobial Resistance Surveillance Trial (CARST) from 2019 to 2020. An antibacterial susceptibility test was performed by using the agar dilution method. CP-EC were detected by the modified carbapenem inactivation method (mCIM), EDTA-modified carbapenem inactivation method (eCIM), and polymerase chain reaction (PCR). Homology analysis was performed by multilocus sequence typing (MLST). A conjugation experiment was performed to verify the transferability of plasmids carrying carbapenemase genes. WGS was conducted to explore the gene-environment of the carbapenemase gene. Result Of the 780 Escherichia coli isolates, 31 isolates were insensitive to carbapenem with a rate of 4%. Among them, 13 CP-EC isolates had transferability of the blaNDM gene. These isolates belonged to nine distinct sequence types (STs), with some correlation. We found that two (2/13, 15.4%) of the CP-EC isolates that were collected from blood specimens were highly pathogenic and also showed high transferability of the blaNDM gene. In addition, eight (8/13, 61.5%) of the CP-EC isolates were found to be multidrug-resistant. Conclusion With the increasing use of carbapenem, CP-EC isolates accounted for nearly half of the total carbapenem-insensitive Escherichia coli isolates. Our findings highlight the urgent need to pay attention to CP-EC isolates in bloodstream infections and ESBL-producing CP-EC isolates. Based on the One Health concept, we suggest various measures, including the development of bacterial vaccines, antibiotic management, and establishment of better medical environments, to avoid the outbreak of CP-EC.